Choosing the share bond by using qualitative dependent variable models in Turkey - ÇAĞLAYAN AKAY, EBRU; GÜRİŞ, SELAHATTİN (SPRINGER, 2009)
In this paper whether the bond according to a certain criterion for one time period in the future with the classic logit models and for a certain time period in the future with the panel logit model is successful or not have been forecasted. For this purpose financial ratios of the industrial companies listed on Istanbul Stock Exchange in Turkey over the period 1995-2001 were used. The results indicated that different financial data is effective in the different models used for different terms i.e., the models are different for each other.
Keywords: Binary logit model; Fixed effect panel logit model; Forecast strength